GAMBARAN KUALITAS HIDUP ORANG DENGAN HIV/AIDS DI YAYASAN SEBAYA LANCANG KUNING PEKANBARU: OVERVIEW OF QUALITY OF LIFE OF PEOPLE WITH HIV/AIDS AT YAYASAN SEBAYA LANCANG KUNING PEKANBARU - Khoir, Wahyu Alfin; Saputra, Bayu; Rasyid, T. Abdur (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2024)
Introduction: HIV/AIDS (Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome) is one of the diseases that attack the immune system. Damage to the immune system in people with HIV/AIDS makes them susceptible to other diseases (opportunistic infections) that are fatal. This study aims to determine the picture of the quality of life of people with HIV/AIDS at Yayasan Sebaya Lancang Kuning Pekanbaru. Method: This research method is a quantitative research with a descriptive design of a survey approach. The respondents in this study were 112 people with a ≤ age of 18 years diagnosed with HIV/AIDS. The analysis used was univariate analysis. The sampling technique used consecutive sampling within a period of 1 month with the research instrument used was the WHOQOL HIV - BREEF questionnaire. Result: The results of the study on the quality of life (QoL) of people with HIV/AIDS obtained a median age of 31 years. The majority of men amounted to 88 respondents (78.6%), respondents had the most recent high school education amounting to 65 respondents (58%). Long diagnosed with HIV/AIDS > 3 years amounted to 60 respondents. The majority of unmarried marital status amounted to 74 respondents (66.1%). Based on job characteristics, the majority of respondents worked 81 respondents (72.3%). The QoL outcomes of people with HIV/AIDS at Yayasan Sebaya Lancang Kuning Pekanbaru is high at 60 (53.6%). while the results of poor QoL amounted to 52 (46.4%). Conclusion: The majority of the QoL of people with HIV/AIDS at Yayasan Sebaya Lancang Kuning Pekanbaru in the high category. It is recommended that the Sebaya Lancang Kuning Pekanbaru Foundation can form a spiritual support group for PLHIV accompanied by.